Upaya Peningkatan Kesehatan Remaja Dalam Menghindari Kehamilan Diluar Nikah - Lasmi Handayani; Heni Suraida Rahayu; Christy Olivia; Dwi Wachyu N; Ika Meirini; Nila Qurniasih (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The phenomenon of teenagers getting pregnant out of wedlock, especially in Indonesia, is increasing. The risk of pregnancy out of wedlock physiologically, psychologically and socially causes several impacts, one of which is the emergence of depression due to the negative stigma that society places on these teenagers. As for the analysis of the causes of pregnancy that occurs, one of them is the lack of information regarding reproductive health in adolescents, so the solution is to carry out reproductive health education activities for adolescents regarding pregnancy outside of marriage. This community outreach activity was carried out on January 12 2024 at the Paguyuban Middle School in Bandar Agung Village and was attended by 40 people. The methods used in this activity are lectures, discussions, direct demonstrations and questions and answers and before and after this activity a pretest and posttest are given. So with this activity it is hoped that the community, especially teenagers, will be able to understand and realize the importance of knowledge about pregnancy outside of marriage. The aim of this outreach to the community is to synthesize creative ideas through educational outreach programs by carrying out preventive and promotive efforts in preventing and dealing with out-of-wedlock pregnancies among teenagers.